A case control study of nasal passage changes in repaired cleft lip and/or plate deformity with persons without any such deformity - Ahmad, M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Cleft lip with or without an associated cleft palate (CLP) is one of the most common congenital birth defects. Both the frequency with which it occurs and the high psychosocial and financial costs associated with CLP contribute to a significant public health interest in the condition. The aim of the present study is to assess the nasal passage changes in repaired cleft lip and/or plate deformity with persons without any such deformity. Methods: It was a case-control study comprising of 2 groups. Carried out in 25 patients with 15 years and above admitted in plastic surgery or ENT Department of Gandhi Memorial and associated hospital or in patients in whom surgery has been performed earlier. After taking written informed consents from family members or legal guardians detailed history with presenting complaints was taken. Data entry and statistical analysis were performed using the Microsoft Excel and SPSS windows version 16.0 software. Tests of significance like Chi-square test are applied to find out the results. Results: Mean age of cases in 25.8 years and control 28.7. Deviation of nasal septum was present in 68% cases and 28% in control. Nasal obstruction left side in higher in cases than control. Deviation of nasal septum (L) was more common in cleft because most of the patient had cleft in left side. Caudal dislocation was also common in cleft. It was opposite to the side of cleft. It was common on right side because most of the patients have cleft on left side. Conclusions: Nasal airflow analysis would be particularly helpful in such investigations. The commonest presenting symptom is nasal obstruction. It is due to deviation of nasal septum.